Influence of wet etching time cycles on morphology features of thin porous Anodic Aluminum oxide (AAO) template for nanostructure's synthesis. (December 2015) - Chahrour, Khaled M.; Ahmed, Naser M.; Hashim, M.R.; Elfadill, Nezar G.; Al-Diabat, Ahmad M.; Bououdina, M.
Abstract: This study examines the influence of chemical wet etching time cycles on the morphological features of thin porous AAO template. Pore widening via wet-etching treatment at room temperature was found to modify the pore quality of AAO template and reduces the barrier layer on the bottom of AAO pore array in order to facilitate uniform electrodeposition of nanostructures onto AAO template. High quality AAO pore arrays with different mean pore diameters (64, 70, and 87 nm) were prepared under controllable pore-widening time cycles of 10, 30 and 45 min at room temperature, respectively. The AAO templates and the produced Cu nanorods were characterized using FESEM, EDX, XRD and AFM. The results indicate that the morphology of the aligned arrays of Cu nanorods is strongly affected by the duration of etching and the removal of AAO template. This study showed that the optimum etching duration required to maintain the aligned nanorods without any fracture is approximately 5 min. In addition, the regular hemispherical concave Al surface ensuring the self-ordering of AAO pore can be established when striping is employed for 45 min. Thus, it can be inferred that the duration of wet etching treatment (striping) of Al oxide film performed after the first-step anodization plays a vital role in the final arrangement of nanopores. Highlights: The wet etching (striping) of the AAO film after the first-step anodization plays an essential role in the final arrangement of nanopores. Fabricate highly ordered AAO templates of desired pore diameters by controllable chemical pore-widening time at room temperature. The morphologies of the aligned arrays of Cu nanorods strongly affected by the etching times as removal of AAO template were investigated.